2002
DOI: 10.1074/jbc.m203271200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin Leads to Superoxide Formation by Enzymatic and Non-enzymatic Redox Cycling

Abstract: The ansamycin antibiotic geldanamycin has frequently been used as an inhibitor of heat shock protein 90 (Hsp90), and this agent has been widely employed as a probe to examine the interactions of Hsp90 with endothelial nitric-oxide synthase. Geldanamycin contains a quinone group, which may participate in redox cycling. When geldanamycin was exposed to the flavin-containing enzyme cytochrome P-450 reductase, both semiquinone and superoxide (O 2 . ) radicals were detected using electron spin resonance. . , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(49 citation statements)
references
References 27 publications
2
46
1
Order By: Relevance
“…The role of Hsp90 as a "switch" from superoxide to NO production was also demonstrated in neural NO synthase (48). However, later studies extended these findings and showed that geldanamycin is able to increase superoxide production independently of endothelial NO synthase activation both in in vivo and in vitro systems, possibly by its quinone group, which may participate in redox cycling (21). Similar data were reported on neural NO synthase (20).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The role of Hsp90 as a "switch" from superoxide to NO production was also demonstrated in neural NO synthase (48). However, later studies extended these findings and showed that geldanamycin is able to increase superoxide production independently of endothelial NO synthase activation both in in vivo and in vitro systems, possibly by its quinone group, which may participate in redox cycling (21). Similar data were reported on neural NO synthase (20).…”
Section: Discussionsupporting
confidence: 67%
“…2B), which suggested that the two effects are not independent from each other. Reaching this point in our experiments the first results of geldanamycininduced superoxide generation appeared (20,21). What if shaking provided an additional oxygen inducing a larger amount of superoxides?…”
Section: Geldanamycin Induces An Accelerated Lysis Of Jurkatmentioning
confidence: 89%
See 2 more Smart Citations
“…anion (8). Superoxide could interact with NO to form peroxynitrite and reduce the amounts of NO that are available to interact with sGC independent of the actions of geldanamycin on HSP90.…”
Section: Fig 7 Fluorescent Colocalization Of Hsp90 and Sgc In Baecsmentioning
confidence: 99%